1997
DOI: 10.1038/sj.ijo.0800543
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Cardiorespiratory Fitness Attenuate Age-related Weight Gain in Healthy Men and Women: The Aerobics Center Longitudinal Study

Abstract: OBJECTIVE: To determine the longitudinal relation of change in cardiopulmonary ®tness to subsequent change in body weight in a cohort of healthy middle-aged adults. DESIGN: Prospective cohort study. SUBJECTS: Participants were 4599 men and 724 women (43 AE 9 y) receiving at least three medical examinations between 1970 and 1994. Examinations included assessment of cardiorespiratory ®tness by maximal exercise tests and measurement of body weight. MEASUREMENTS: Change in ®tness was calculated as the difference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 13 publications
3
54
1
2
Order By: Relevance
“…Compared to the nationally representative NHANES data 5 the HRFP subjects exhibited less weight gain over time, but their weight changes were similar to those reported by a longitudinal study of active members of the Aerobics Center in Dallas, Texas. 29 The average yearly change in weight of the HRFP subjects was about 0.07 kg (0.15 lb) and 0.27 kg (0.60 lb) for the men and women, respectively, compared with the average yearly weight increase for the Aerobics Center sample of 0.08 kg (0.18 lb) for the men and 0.20 kg (0.44 lb) for the women. In general, the HRFP subjects tended to maintain a moderate to high level of physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the nationally representative NHANES data 5 the HRFP subjects exhibited less weight gain over time, but their weight changes were similar to those reported by a longitudinal study of active members of the Aerobics Center in Dallas, Texas. 29 The average yearly change in weight of the HRFP subjects was about 0.07 kg (0.15 lb) and 0.27 kg (0.60 lb) for the men and women, respectively, compared with the average yearly weight increase for the Aerobics Center sample of 0.08 kg (0.18 lb) for the men and 0.20 kg (0.44 lb) for the women. In general, the HRFP subjects tended to maintain a moderate to high level of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies, one on cross-sectional survey data from a large group of male runners, 43 the other on longitudinal data from members of a large healtha®tness center, 29 showed that long-term maintenance of the level of exercise and aerobic power attenuates but does not prevent aging-related weight gain. The authors of both studies suggested that without exercise there would be even greater weight gain, and preventing weight gain may actually require an increase in exercise with aging.…”
Section: Discussionmentioning
confidence: 99%
“…29 It has also been shown that improvements in fitness reduce the risk of age-related weight gain in middleaged adults. 30 In older adults, increased physical activity energy expenditure may be important for body weight maintenance by counteracting both an age-related decrease in total energy expenditure as well as a predisposition toward positive energy balance as a consequence of acute age-related energy intake dysregulation. Future research is necessary to determine if increased physical activity energy expenditure in older adults can improve long-term accuracy of energy intake regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, they support the hypothesis that even low-tomoderate intensity physical activities, feasible by most adults, are bene®cial for preventing weight gain with age. Several large-scale observational studies indicate a relationship between baseline or improvement in physical activity 17±23 or cardiorespiratory ®tness 24,25 and subsequent weight gain or risk of becoming overweight. As in our cohort, regular performing of high-intensity activity during leisure-time was Data were adjusted for centre, age group, marital status, educational level, employment status, socio-occupational class, following a weight-control diet, alcohol consumption, smoking status and occupational-related PAE.…”
Section: Discussionmentioning
confidence: 99%